The effect of smoking on atrial and ventricular functions in healthy subjects: A speckle tracking echocardiography study - ÖZBEN SADIÇ, BESTE; SAYAR, NURTEN; CAN BOSTAN, ÖZGE; BAYRAM, TUBA (WILEY, 2020)
Purpose Smoking is a well-known risk factor for coronary artery diseases. It is also associated with nicotine-induced myocardial dysfunction. The aim of this study was to evaluate the right and left atrial and ventricular functions in apparently healthy smokers. Methods We included consecutively 80 healthy smokers (56 males, mean age:35.5 +/- 8.4 years) and 70 healthy nonsmokers (44 males, mean age:33.9 +/- 9.5 years). None of the subjects had any additional cardiovascular risk factor other than smoking. The right and left atrial and ventricular functions were assessed by both conventional and speckle tracking echocardiography. Results Although there was no significant difference in left ventricular ejection fraction, the smokers had significantly lower ventricular global longitudinal strain than controls (-19.9 +/- 2.0% vs -21.2 +/- 1.9%,P < .001 and -18.4 +/- 2.1% vs -21.8 +/- 2.2%,P < .001, respectively, for the left and right ventricle). Smokers had also lower atrial reservoir and conduit strains: 35.9 +/- 11.1% vs 40.2 +/- 11.2%,P= .022 and 16.7 +/- 6.8% vs 19.4 +/- 6.8%,P= .016, respectively, for the left atrium, and 33.0 +/- 10.6% vs 37.6 +/- 11.2%,P= .011 and 15.2 +/- 5.6% vs 18.0 +/- 6.3%,P= .004, respectively, for the right atrium). Conclusion Even in apparently healthy people with no other cardiovascular risk factors, smoking is associated with impaired atrial and ventricular functions.
Keywords: atrium; smoking; speckle tracking echocardiography; ventricle; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; HEART; RECOMMENDATIONS; DYSSYNCHRONY; DYSFUNCTION; UPDATE; STRAIN